2022
DOI: 10.1038/s41379-021-00884-w
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative comparison of PD-L1 IHC assays against NIST standard reference material 1934

Abstract: Companion diagnostic immunohistochemistry (IHC) tests are developed and performed without incorporating the tools and principles of laboratory metrology. Basic analytic assay parameters such as lower limit of detection (LOD) and dynamic range are unknown to both assay developers and end users. We solved this problem by developing completely new tools for IHC - calibrators with units of measure traceable to National Institute of Standards & Technology (NIST) Standard Reference Material (SRM) 1934. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Overall, cytologic specimens appear to be acceptable specimens for PD‐L1 analysis especially when formalin fixed paraffin embedded cell block specimens are evaluated using the TPS for evaluation 9–13,20,22,24,34–70 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, cytologic specimens appear to be acceptable specimens for PD‐L1 analysis especially when formalin fixed paraffin embedded cell block specimens are evaluated using the TPS for evaluation 9–13,20,22,24,34–70 …”
Section: Discussionmentioning
confidence: 99%
“…Quantitative comparison of PD-L1 immunohistochemistry assays with standard reference materialWhile non-quantitative evaluation of immunohistochemically stained specimens can be adequately controlled by appropriate similarly processed known positive and known negative specimens, quantitative and semi-quantitative assays for antigens such as estrogen receptor, progesterone receptor, and PD-L1 requires a more appropriate standard reference material. Sompuram et al69 have discussed the need for such a standard reference material. They demonstrated the utility of calibrators traceable to the National Institute of Standards and Technology (NIST) standard reference material 1934.…”
mentioning
confidence: 99%
“…demonstrated that SP142 is characterized by a very high LOD compared to other approved and laboratory-developed test (LDT) assays and therefore is less sensitive. In particular, these authors showed that SP263 and SP142 do not show overlap in their dynamic range while 22C3 shows little overlap with the analytical performance of SP142 ( 27 ). These data explain the inability to harmonize the SP142 assay with either the SP263 or the 22C3 assay.…”
Section: Discussionmentioning
confidence: 99%
“…NIST has recently worked with a few academic centers and reagent manufacturers on a single-target basis for known predictive biomarkers (e.g., PD-L1, ER, p53— Atha et al, 2010 ; Torlakovic et al, 2021 ; Sompuram et al, 2022 ) for the creation of tools linked to international standards enabling IHC measurement traceability and their validation by IPT/EQA programs. A consensus call supported by CAP, NIST, and FDA to develop a HER2 standard reference material occurred prior but no test standard emerged ( Hammond et al, 2003 ).…”
Section: Safety and Quality Standardsmentioning
confidence: 99%